Control Interlayer Stacking and Chemical Stability of Two-Dimensional Covalent Organic Frameworks via Steric Tuning - Wu, Xiaowei; Han, Xing; Liu, Yuhao; Liu, Yan; Cui, Yong (Journal of the American Chemical Society, 2018)
Layer stacking and chemical stability are crucial for two-dimensional covalent organic frameworks (2D COFs), but are yet challenging to gain control. In this work, we demonstrate synthetic control of both the layer stacking and chemical stability of 2D COFs by managing interlayer steric hindrance via a multivariate (MTV) approach. By co-condensation of triamines with and without alkyl substituents (ethyl and isopropyl) and a di- or trialdehyde, a family of two-, three-, and four-component 2D COFs with AA, AB, or ABC stacking is prepared. The alkyl groups are periodically appended on the channel walls and their contents, which can be synthetically tuned by the MTV strategy, control the stacking model and chemical stability of 2D COFs by maximizing the total crystal stacking energy and protecting hydrolytically susceptible backbones through kinetic blocking. Specifically, the COFs with higher concentration of alkyl substituents adopt AB or ABC stacking, while lower amount of functionalities leads to the AA stacking. The COFs bearing high concentration of isopropyl groups represent the first identified COFs that can retain crystallinity and porosity in boiling 20 M NaOH solution. After postsynthetic metalation with an iridium complex, the 2,2′-bipyridyl-derived COFs can heterogeneously catalyze C–H borylation of arenes, whereas the COF with isopropyl groups exhibits much higher activity than the COFs with ethyl groups and nonsubstituents due to the increased porosity and chemical stability. This work underscores the opportunity in using steric hindrance to tune and control layer stacking, chemical stability and properties of 2D COFs.